Wages, Prices, the Natural Wage and Income Distribution - Gutman, Peter M. (Journal of Income Distribution®, 2001)
In a world of oligopoly and monopolistic competition, prices are essentially set using a markup principle. Real wages are money wages divided by average price level, which depends on average markup level. In the short run, as markups and real wages change when expectations are not correct, income distribution changes. The natural real wage is the real wage at full employment (natural rate of unemployment NAIRU). Even without economic growth the natural real wage, hence income distribution, can change. With economic growth, the natural real wage occurs at: lower rates of unemployment in dynamic societies; higher rates of unemployment in sluggish societies.